An Unprecedented Straightforward Synthesis of Chiral Pyrrolo[3,4-b]quinolone and Pyrrolo[3,2-b]quinolone Backbones Starting from trans-4-Hydroxy-L-proline - Sébastien Comesse; Adam Daïch (Journal of Chemistry)
The straightforward synthesis of pyrrolo[3,4-b]quinolone and pyrrolo[3,2-b]quinolone backbones, which can be found in molecules exhibiting anticancer activities, is presented. The key step of the process is an efficient and unprecedented Friedländer condensation between an oxoproline carbamate, obtained in 3 steps and good yield starting from commercially available and relatively cheap trans-4-hydroxy-L-proline, and various 2-amino-substituted carbonyl derivatives. It was demonstrated that the formation of the two possible regioisomers was fully triggered by both the R substituent onto the 2-amino-substituted carbonyl compounds and the ester function onto the oxoproline carbamate. Thus, in some cases, a complete regiocontrol for the Friedländer reaction could be attained.